KATA SAPAAN BAHASA SUKU ANAK DALAM DESA BUKIT SUBAN KECAMATAN AIR HITAM KABUPATEN SAROLANGUN - Sainil Amral; Eka Sulistiani (Universitas Batanghari, 2021)
This research aims to describe the form and function of the words of the Language of Suku Anak Dalam di Desa Bukit Suban Kecamatan Air Hitam Kabupaten Sarolangun. This research uses the qualitative descriptive method. The data in this study is in the form of oral speech about greetings used to greet the speaker community in daily communication in Suku Anak Dalam di Desa Bukit Suban Kecamatan Air Hitam Kabupaten Sarolangun. The results of this research are in the form of descriptions of kinship and non-kinship greeting forms. Thus it can be said that the form of the kinship of Bahasa Suku Anak Dalam Desa Bukit Suban Kecamatan Air Hitam Kabupaten Sarolangun there are several types, namely the word direct kinship greeting in sequence such as the word